Sulodexide improves pain-free walking distance in patients with lower extremity peripheral arterial disease: A systematic review and meta-analysis. (February 2020) - Gaddi, Antonio Vittorino; Capello, Fabio; Gheorghe-Fronea, Oana Florentina; Fadda, Simone; Darabont, Roxana Oana
Peripheral arterial disease is associated with very high cardiovascular risk. The main symptom is intermittent claudication, which strongly affects the quality of life. Therefore, treatment goals in peripheral arterial disease consist of the reduction of cardiovascular events and the relief of symptoms. An increase in pain-free walking distance, evaluated based on the Initial Claudication Distance, was also a strong positive prognostic factor in patients with peripheral arterial disease. Our objective was to reassess whether sulodexide is effective in improving Initial Claudication Distance. For this, we searched the literature according to the PRISMA checklist for double blind clinical trials assessing the improvement in the Initial Claudication Distance after 90 days of standard therapeutic regimen with sulodexide in adult patients with peripheral arterial disease. We found and assessed for bias in 11 studies eligible for review and meta-analysis. Data extracted from those studies favoured the sulodexide group, showing an overall difference in Initial Claudication Distance of +68.9 (CI 95%; ± 11.9 m) at the end of treatment (p < 0.001). According to this review, sulodexide is effective in improving Initial Claudication Distance and consequently the quality of life in patients with peripheral arterial disease. Further studies are needed to assess the effects of this drug on disease progression in asymptomatic patients with peripheral arterial disease.